2020
DOI: 10.3390/rs12121952
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Machine Learning Methods for Urban Vegetation Mapping Using Multitemporal Sentinel-1 Imagery

Abstract: Mapping of green vegetation in urban areas using remote sensing techniques can be used as a tool for integrated spatial planning to deal with urban challenges. In this context, multitemporal (MT) synthetic aperture radar (SAR) data have not been equally investigated, as compared to optical satellite data. This research compared various machine learning methods using single-date and MT Sentinel-1 (S1) imagery. The research was focused on vegetation mapping in urban areas across Europe. Urban vegetation was clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 105 publications
(109 reference statements)
1
31
0
Order By: Relevance
“…The Sentinel-1 SAR GRD dataset was collected using the interference wide-band (IW) mapping mode, with a spatial resolution of 10 m, a width of 250 km and an average incidence angle of 30-45 • . Each Sentinel-1 image stored by the GEE platform, which had been preprocessed using the European Space Agency's (ESA) Sentinel-1 Toolbox including orbit restitution, thermal noise removal, terrain correction and radiometric calibration [39][40][41].…”
Section: Sentinel-1 Sar Image and Preprocessingmentioning
confidence: 99%
“…The Sentinel-1 SAR GRD dataset was collected using the interference wide-band (IW) mapping mode, with a spatial resolution of 10 m, a width of 250 km and an average incidence angle of 30-45 • . Each Sentinel-1 image stored by the GEE platform, which had been preprocessed using the European Space Agency's (ESA) Sentinel-1 Toolbox including orbit restitution, thermal noise removal, terrain correction and radiometric calibration [39][40][41].…”
Section: Sentinel-1 Sar Image and Preprocessingmentioning
confidence: 99%
“…The difference in the performance of classification algorithm have been demonstrated using different methods. (Gašparović and Dobrinić, 2020) used McNemar's χ 2 test to compare the performance of classifier algorithms, including XGB, SVM and Random Forest (RF). In this study we also compare the performance of the three classifiers, namely Naive Bayes, Decision Tree (DT) and Random Forest (RF) in a total of 84 classifications carried out across the multi-date images.…”
Section: Discussionmentioning
confidence: 99%
“…(1) ALS data allowed for an automated and more accurate identification of AAL in terms of classification accuracy (>90%) and spatial resolution (<1.0 m) than did other RS platforms [53][54][55][56][57][58][59][60][61][62][63][64]. Potential improvements in process of AAL identification may be achieved using some qualitative variable of ALS data (e.g., intensity) or alternatively through multispectral ALS data [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also demonstrated the potential of radar data as an alternative to optical images for the identification of AAL. Synthetic aperture radar systems provided all-weather mapping capability [64], but the overall accuracy of AAL identification varied from 63% to 93% [18,65] and thus did not exceed the limits of optical images. Moreover, the limited spatial resolution of both optical and radar images may not be sufficient to identify the fragmented occurrence and dynamics of land abandonment.…”
Section: Spatial Identification Of Abandoned Agricultural Landmentioning
confidence: 99%